Coping Styles and Self-Regulation Abilities as Predictors of Anxiety - Kalamazh Ruslana; Voloshyna-Narozhna Viktoriia; Tymoshchuk Yelyzaveta; Balashov Eduard (Insight: the psychological dimensions of society, 2024)
This study aims to determine whether coping mechanisms and self-regulation abilities are predictors of trait (T-Anxiety) and state anxiety (S-Anxiety). Method: Data collection was conducted on a student sample (N = 302), who completed the State-Trait Anxiety Inventory (STAI), the Meta-worry Questionnaire (MWQ), the Metacognition Questionnaire-30 (MCQ-30), the Multi-Modal Coping Inventory (MMCI), the Ways of Coping Questionnaire (WCQ) and the Action Control Scale (ACS-90). Correlations and hierarchical multiple regression analyses were conducted. Results. It was found that the coping strategies determined on the basis of the BASIC Ph model are the strongest predictors of T-Anxiety and S-Anxiety, explaining 39.6% and 25.0% of the variance, respectively. Coping strategies determined by the WCQ were also statistically significant predictors of T-Anxiety and S-Anxiety, explaining 12.1% and 9.9% of the variance, respectively. Self-regulation abilities were identified as significant predictors of T-Anxiety and S-Anxiety, explaining 5.3% and 2.2% of the variance, respectively. Discussion and Conclusions. The research proves the existence of a relationship between a set of variables, such as coping strategies and self-regulation abilities, which are predictors and cause changes in T-Anxiety and S-Anxiety. Іt was established that coping strategies self-regulation abilities are predictors of T-Anxiety and S-Anxiety. Specifically, the use of Belief as a coping style was found to decrease T-Anxiety and S-Anxiety. In contrast, the use of Affect and Imagination as coping styles caused an increase in T-Anxiety, and the use of Imagination as a coping style increased S-Anxiety. In addition, it was established that the use of such a coping strategy as acceptance of responsibility and escape-avoidance increases T-Anxiety. In contrast, the use of the coping strategy of problem-solving planning predicts a decrease in T-Anxiety and S-Anxiety. The obtained results also indicate that increasing self-regulation indicators with a prospective and decision-related action orientation vs. hesitation (AOD) predicts a decrease in T-Anxiety and S-Anxiety.